2015
DOI: 10.1002/ijc.29663
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors that interact with p53 and Mdm2

Abstract: The tumor suppressor p53 is activated upon cellular stresses such as DNA damage, oncogene activation, hypoxia, which transactivates sets of genes that induce DNA repair, cell cycle arrest, apoptosis, or autophagy, playing crucial roles in the prevention of tumor formation. The central regulator of the p53 pathway is Mdm2 which inhibits transcriptional activity, nuclear localization, and protein stability. More than 30 cellular p53-binding proteins have been isolated and characterized including Mdm2, Mdm4, p300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 85 publications
(255 reference statements)
3
76
0
Order By: Relevance
“…The DMP1 consensus is located −2.3 kb and −0.31 kb of ARF and −4.04 kb and −1.40 kb of INK4a in humans. Both of these are Dmp1 target genes (Dmp1 reviewed in 7, 96–98) although the mode of regulation is different (36). …”
Section: Figurementioning
confidence: 99%
“…The DMP1 consensus is located −2.3 kb and −0.31 kb of ARF and −4.04 kb and −1.40 kb of INK4a in humans. Both of these are Dmp1 target genes (Dmp1 reviewed in 7, 96–98) although the mode of regulation is different (36). …”
Section: Figurementioning
confidence: 99%
“…The human DMTF1 gene is located on chromosome 7p21, a region frequently deleted in breast cancer, acute myeloid leukemia (AML), and myelodysplastic syndrome (MDS) [8,67,68,69]. DMTF1 is highly conserved between humans and mice, with 95% similarity in amino acid sequences.…”
Section: Cyclin D-binding Myb-like Transcription Factor 1 (Dmtf1):mentioning
confidence: 99%
“…Of note, both Dmp1 +/− and Dmp1 −/− mice showed acceleration of oncogene-induced tumor development with no significant differences in survival between the two cohorts, suggesting that Dmp1 is haplo-insufficient for tumor suppression (19, 34, 35; reviewed in 46). We recently reported that Dmp1 physically interacts with p53 to neutralize the known functions of Mdm2 (or HDM2), namely ubiquitination, nuclear-cytoplasmic transport, and suppression of transport (47), a very unique property among p53/Mdm2-binding transcription factors (48). The h DMP1 locus encodes at least three splicing variants -h DMP1α, β, and γ with antagonizing functions (4951, reviewed in 52).…”
Section: Introductionmentioning
confidence: 99%